Emphysematous Gastritis in a Patient with Untreated Cyclic Vomiting Syndrome. Issue 1 (2018) - Robinson, Sara L.; Sadowski, Brett W.; Eickhoff, Christa; Mitre, Edward; Young, Patrick E.
ABSTRACT : N/A: Emphysematous gastritis (EG) is an uncommon and potentially fatal disease characterized by gastric pneumatosis in the setting of infection. While this disease has been described in the literature, it has not previously been identified as a potential complication of cyclic vomiting syndrome. We describe a patient with a history of cyclic vomiting syndrome who presented acutely ill and was found to have radiographic, endoscopic, and histologic evidence of EG. This case illustrates how an untreated functional bowel disorder can lead to severe and potentially fatal complications.